Financing Higher Education and Moral Hazard: A Systematic Literature Review - Karanović, Goran; Dragičević, Daniel; Olgić Draženović, Bojana (KnE Social Sciences, 2023)
This study differentiates and determines the problem as well as the determinants of moral hazard in financing higher education. Moral hazard is a phenomenon that occurs when financial costs of risks undertaken are being transferred onto a third person. It occurs when a person – individual or institution – acts differently because they are detached from the risks; hence, they consciously enter a risk knowing that someone else has to bear the costs of such behavior. Research on moral hazard has arisen from the fields of finance and insurance; it is related to asymmetric information, the relationship between agent and principal in finance, as well as to irresponsible risk behavior. With this study the authors aim to identify problems that arise in the moral hazard process in higher education financing. The Kitchenham Systematic Literature Review (SLR) approach has been applied in this study, as published in the Clarivate Web of Science Core Collection. The research findings identify scarce theoretical foundation, on the basis of which the authors have carried a couple of research variations. A table of occurrence of moral hazard in higher education financing is presented in this paper, as well as a number of recommendations for further research on this topic. Keywords: moral hazard, higher education, financing, Kitchenham Systematic Review